2020
DOI: 10.1021/acsbiomaterials.9b01487
|View full text |Cite
|
Sign up to set email alerts
|

Coating Topologically Complex Electrospun Fibers with Nanothin Silk Fibroin Enhances Neurite Outgrowth in Vitro

Abstract: Electrospun poly-l-lactic acid (PLLA) fibers are commonly used for tissue engineering applications because of their uniform morphology, and their efficacy can be further enhanced via surface modification. In this study, we aimed to increase neurite outgrowth along electrospun fibers by coating with silk fibroin (SF), a bioinert protein derived from Bombyx mori cocoon threads, shown to be neurocompatible. Aligned PLLA fibers were electrospun with smooth, pitted, and divoted surface nanotopographies and coated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
(89 reference statements)
2
15
1
Order By: Relevance
“…In this study, we successfully demonstrate patterned SFbased NGCs synthesis and their successful outcomes for PNI repair. Some previous works support our results, demonstrating that longitudinal patterns, for example in the form of fibres, can promote neurite outgrowth [36][37][38]. Mechanical studies demonstrated the optimal Young's modulus of the developed conduits, as well as their kinking and suturability resistance.…”
Section: Introductionsupporting
confidence: 90%
“…In this study, we successfully demonstrate patterned SFbased NGCs synthesis and their successful outcomes for PNI repair. Some previous works support our results, demonstrating that longitudinal patterns, for example in the form of fibres, can promote neurite outgrowth [36][37][38]. Mechanical studies demonstrated the optimal Young's modulus of the developed conduits, as well as their kinking and suturability resistance.…”
Section: Introductionsupporting
confidence: 90%
“…In addition to changing larger-scale features of the electrospun fibers, such as fiber orientation and diameter, researchers have investigated the impact of adding smaller nanotopographical features, such as pits, divots, and grooves to fibers on nervous system regeneration [ 25 , 127 , 128 , 129 ]. Little has been done to investigate the effect of these nano-scale features on cell differentiation into the Schwann cell lineage or Schwann cell maturation, adhesion, and proliferation.…”
Section: Peripheral Nervous System Glia and Electrospun Fibersmentioning
confidence: 99%
“…Surface wettability was assessed for each fiber type using a Kruss DSA 100 goniometer as described previously (Ziemba et al, 2020) to determine if the inclusion of fingolimod into the electrospun fibers changed the fiber surface chemistry. At least three drops were assessed per replicate.…”
Section: Electrospun Fiber Surface Wettability Assessmentmentioning
confidence: 99%